Assessment of the banking sector's exposure to hydrometeorological events in Costa Rica - Irene Alvarado-Quesada; Jose Pablo Barquero-Romero; Cristian Sancho-Brenes (Latin American Journal of Central Banking)
This study examines, for the first time, the exposure of the credit portfolio of the banking system in Costa Rica to hydrometeorological events, specifically excess rainfall events, with a focus on firm credit at the canton level. We propose a credit risk indicator to identify cantons with credit portfolios that are more affected by rainfall events. Moreover, we introduce a novel approach with respect to firm level data to assign a single productive location to firms with two or more establishments. We find that cantons with the highest number of excess rainfall events represent a small share of the average credit balance of the country. Furthermore, we observe that the top three cantons with the highest credit risk score are driven by economic activities that are not expected to be notably vulnerable to extreme rainfall.